Sexual Activity and Physical Tenderness in Older Adults: Prevalence and Associated Characteristics from a Belgian Study. Issue 4 (27th February 2022) - Cismaru-Inescu, Adina; Hahaut, Bastien; Adam, Stéphane; Nobels, Anne; Beaulieu, Marie; Vandeviver, Christophe; Keygnaert, Ines; Nisen, Laurent
ABSTRACT: Background: Despite the World Health Organization calling for sexuality to be recognized as an aspect of well-being, no studies have explored sexual activity and physical tenderness in older adults aged ≥ 75 years in Belgium or those aged ≥ 85 years worldwide. Aim: To assess the prevalence and predictors of sexual activity and physical tenderness in a sample of older adults. Methods: Using data from a Belgian cross-sectional study on sexual violence (UN-MENAMAIS), information on sexual activity, physical tenderness, and associated characteristics was collected during structured face-to-face interviews with older adults living in the community, assisted living facilities, or nursing homes. Cluster random probability sampling with a random route-finding approach was used to select the participants. Outcomes: Current sexual activity and physical tenderness in the previous 12 months, sociodemographic characteristics, chronological age, subjective age, number of sexual partners, sexual satisfaction, attitudes toward sexuality in later life, quality of life, and lifetime sexual victimisation. Results: Among the 511 participants included, 50.3% were in a relationship, mainly living with their partner; 31.3% indicated they were sexually active; and 47.3% of sexually inactive participants reported having experienced forms of physical tenderness in the previous 12 months. Sexual activity was associated with the presence of a partner, satisfaction with sexual life, permissive attitudes regarding sexuality in later life, a younger age, and a lack of disability. Physical tenderness was associated with the presence of a partner, community residency, and permissive attitudes regarding sexuality in later life. Clinical Implications: Raising awareness among the general population, healthcare professionals, and older adults about sexuality in later life could contribute to ending this taboo and should therefore be a priority for society. Strengths and Limitations: Our study fills a gap in the literature regarding sexual activity and physical tenderness in older adults aged ≥ 70 years, including respondents aged up to 99 years. Additionally, we explored different forms of sexual expression beyond intercourse, and face-to-face interviews contributed to the quality of the collected data. The main limitation of this study was the sample size, although the findings were similar to recent statistical indicators in Belgium. Conclusion: One in 3 older adults aged ≥ 70 years living in Belgium are sexually active. These findings provide an opportunity to inform the general public and older adults about later life sexuality and to educate healthcare professionals about aging sexuality to increase discussions and avoid assumptions of asexuality in later life.